Acute and Chronic Management of Ocular Disease in Stevens Johnson Syndrome/Toxic Epidermal Necrolysis in the USA - Metcalfe, Derek; Iqbal, Omer; Chodosh, James; Bouchard, Charles S.; Saeed, Hajirah N. (Frontiers in Medicine, 2021)
Stevens Johnson syndrome and toxic epidermal necrolysis are on a spectrum of a severe, immune-mediated, mucocutaneous disease. Ocular involvement occurs in the vast majority of cases and severe involvement can lead to corneal blindness. Treatment in the acute phase is imperative in mitigating the severity of chronic disease. Advances in acute treatment such as amniotic membrane transplantation have shown to significantly reduce the severity of chronic disease. However, AMT is not a panacea and severe chronic ocular disease can and does still occur even with aggressive acute treatment. Management of chronic disease is equally critical as timely intervention can prevent worsening of disease and preserve vision. This mini-review describes the acute and chronic findings in SJS/TEN and discusses medical and surgical management strategies.